Enablers and Consequences of Exploitative Working Relationships in Healthcare Sector - Costa, S.; Coyle-Shapiro, J. A. M.; Oliveira, S. (Academy of Management, 2024)
Exploitation in the workplace, despite advancements in labor protection may be more prevalent than one would anticipate. Employee exploitation can occur when organizations make decisions that promote serving their own interests at the expense of employees’ welfare. Essential workers such as those that work in healthcare may be susceptible to exploitative employer practices given the caring orientation of their jobs yet at the same time, their exposure to high demands and risks with low pay This paper sheds light on the nature of exploitation amongst healthcare workers. An interpretative grounded theory study was conducted using 32 in-depth interviews with healthcare professionals including physicians, nurses, and technicians. The study revealed that these workers feel exploited by their organization. Enabling factors such as a sense of calling, dedication to their job and a desire to make a contribution to society facilitate employees’ susceptibility to being taken advantage of by their organization. Our findings also reveal that workers experience different types of exploitation: relational and structural. The former originates in the relationship with the organization and the latter is associated with exploitative human resource practices. Finally, the results also show that an exploitative employee-organization relationship carries emotional, behavioral and health-related consequences. This study contributes to understanding the experience of exploitative work relationships in the healthcare sector, which is a critical issue in our society and a matter of public concern.